Cultural adaptation and psychometric evaluation of the Yoruba version of the Health Literacy Questionnaire - Mbada, C. E.; Johnson, O. E.; Oyewole, O. O.; Adejube, O. J.; Fatoye, C.; Idowu, O. A.; Odeyemi, R. V.; Akinirinbola, K. B.; Ganiyu, D.; Fatoye, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Health literacy is an important multidimensional concept of public health concern and a determinant of health outcomes and access to healthcare which requires robust measurement. The objective of this study was to culturally adapt and establish the psychometric properties of the Yoruba version of the Health Literacy Questionnaire.Methods. A cross-sectional survey of Nigeria Yoruba speaking adults was conducted with the Health Literacy Questionnaire following its translation and adaptation. Data were subject to psychometric evaluation (confirmatory factor analysis, composite reliability, Cronbach’s alpha, intra class correlation) and association with sociodemographic variables.Results. A total of 258 adults with mean age 26.7 years participated in the study. The easiest scale to score highly was ‘Actively managing my health’ and hardest was ‘Ability to find good health information’ and ‘Navigating the healthcare system’. Six one-factor models fitted well without correlated residuals but the other three had a good fit after model modification. Composite reliability and Cronbach’s α of ≥ 0.7 were observed for all scales, suggesting good internal consistency of the scales. Test-retest reliability of the Yoruba translation of the Health Literacy Questionnaire was moderate to good in all scales, intra class correlation ranging from 0.66 to 0.76.Conclusion. The Health Literacy Questionnaire was successfully translated and culturally adapted and demonstrated good content and construct validity and high composite reliability. The Yoruba translation of the Health Literacy Questionnaire has the potential of being a useful clinical tool for the assessment of health literacy, especially among Yoruba speaking community of Nigeria. Thereby helping to improve the health outcomes through access to healthcare.